Regional impact of Early Cretaceous tectono‐magmatic uplift in the Arctic: Implications of new data from eastern North Greenland. (29th December 2020) - Ineson, Jon R.; Hovikoski, Jussi; Sheldon, Emma; Piasecki, Stefan; Alsen, Peter; Fyhn, Michael B. W.; Bjerager, Morten; Dybkjær, Karen; Guarnieri, Pierpaolo; Lauridsen, Bodil W.; Nøhr‐Hansen, Henrik; Pedersen, Gunver K.; et al.
Abstract: Evaluation of the regional geotectonic impact of the High Arctic Large Igneous Province (HALIP) in the present‐day northern Atlantic region has been hindered by poor correlation between the Svalbard–Barents Shelf region and eastern North Greenland. New sedimentological and biostratigraphic data from Peary Land and Kronprins Christian Land (Kilen), North Greenland reveal that the Lower Cretaceous palaeogeographic and sequence stratigraphic development of this area is closely comparable to that of Svalbard. The succession records Hauterivian – early Barremian regional uplift and emergence followed by fluvial sedimentation and subsequent transgression in the late Barremian – early Aptian. Recognition of this tectonically forced regression in North Greenland provides a link to a coeval well‐known tectonostratigraphic event in the Svalbard region, and hence to regional tectono‐magmatic uplift heralding the HALIP and the initiation of the Amerasia Basin.